Basement membrane collagen IV deficiency promotes abdominal aortic aneurysm formation - L. B. Steffensen (Nature Portfolio, 2021)
Abstract Abdominal aortic aneurysm (AAA) is a complex disease which is incompletely accounted for. Basement membrane (BM) Collagen IV (COL4A1/A2) is abundant in the artery wall, and several lines of evidence indicate a protective role of baseline COL4A1/A2 in AAA development. Using Col4a1/a2 hemizygous knockout mice (Col4a1/a2 +/− , 129Svj background) we show that partial Col4a1/a2 deficiency augmented AAA formation. Although unchallenged aortas were morphometrically and biomechanically unaffected by genotype, explorative proteomic analyses of aortas revealed a clear reduction in BM components and contractile vascular smooth muscle cell (VSMC) proteins, suggesting a central effect of the BM in maintaining VSMCs in the contractile phenotype. These findings were translated to human arteries by showing that COL4A1/A2 correlated to BM proteins and VSMC markers in non-lesioned internal mammary arteries obtained from coronary artery bypass procedures. Moreover, in human AAA tissue, MYH11 (VSMC marker) was depleted in areas of reduced COL4 as assessed by immunohistochemistry. Finally, circulating COL4A1 degradation fragments correlated with AAA progression in the largest Danish AAA cohort, suggesting COL4A1/A2 proteolysis to be an important feature of AAA formation. In sum, we identify COL4A1/A2 as a critical regulator of VSMC phenotype and a protective factor in AAA formation.